Pemanfaatan Web Pemilihan Murid Mengaji dengan Hafalan Terbaik dengan Metode Simple Additive Weighting (SAW) Menggunakan Framework Bootstrap (Studi Kasus : Masjid Jami Al - Karomah) - Bay Haqi; Jonser Sinaga (Jurnal Ragam Pengabdian, 2025)
This community service activity aims to improve the quality of selecting the best Qur’an memorization students at Masjid Jami’ Al-Karomah through the implementation of a web-based Decision Support System (DSS). The system was designed using the Simple Additive Weighting (SAW) method to support objective and measurable assessment processes. The training was delivered directly to Ustadz, Ustadzah, and mosque leaders, covering system login, student data input, score matrix entry, and interpretation of memorization reports. Evaluation results indicated a high level of participant satisfaction: 93.7% enjoyed the training, 92.7% found the materials useful, and 94.7% agreed that the DSS improves the quality of students’ Qur’an memorization. The system significantly assists in streamlining the selection process and encourages students to be more motivated in memorizing. This activity demonstrates that the use of information technology can make a real contribution to improving the governance of community-based religious education.